Diversity of fish fauna and water quality in Murum River below Murum HEP, Belaga, Sarawak - Yeow, Seh Keat (Universiti Malaysia Sarawak (UNIMAS), 2016)
Fish survey and selected water quality parameters sampling were conducted on 231 to 251 of August 2015 and 71 to 91h November 2015 from the downstream of Murum Hydroelectric Powerhouse until Murum River mouth. Currently, there is no information regarding the fish fauna composition at this stretch of the river. Therefore, this study was conducted to determine the effects of water discharge from Murum Powerhouse on the fish fauna and water quality of Murum River below the powerhouse. A total of 270 individuals fish were caught comprising of 21 species from 6 families. The highest number of individuals caught was Cyclocheilichthys apogon (38.57 %), and followed by Kryptopterus lais (10.57 %). The highest species diversity was recorded in station 3 in August 2015 with a value of 1.96, and station 4 in November 2015 with a value of 1.87. The Length-Weight Relationship of 5 selected fish species showed that only Barbonymus schwanenfeldii has positive allometric growth (3.19 ± 0.43) but C. apogon (2.91 ± 0.12) (K= 1.07) and Puntioplites waandersii (2.82 ± 0.15) (K=1.08) showed negative allometric growth. Female Barbonymus schwanenfeldii (4.39±1.46) and both sexes of Pangasius micronemus (female = 5.23±2.46, male = 3.90±3.19) recorded relatively higher GSI value, which indicates that the species may be reproductively active in the area. The HSI value for the combined trips ranged from 0.06 to 0.35 for 15 recorded species. Water quality readings recorded throughout the study showed that temperature ranges from 26.81 °C to 31.38 °C, dissolved oxygen ranges from 4.39 mg/L to 5.97 mg/L, pH ranges from 6.06 to 6.85, conductivity ranges from 31.28 μS/cm to 33.08 μS/cm, turbidity ranges from 0.83 NTU to 84.63 NTU, and transparency ranges from 39.08 cm to 164.96 cm. The impoundment of Murum River may have affected fish fauna composition with reduced diversity along the stretch of river below the HEP due to changes in water quality in the surrounding area.